The correlation between Fischer’s ratio and the risk of cardiac dysfunction in heart failure patients - Qing Fen Zhou; Fan Yang; Qiu Ya Lu; Feng Ru Zhang; Bin Qu; Lin Lu (BMC Cardiovascular Disorders)
Abstract Backgrounds Due to the high mortality and hospitalization rate in chronic heart failure (HF), it is of great significance to study myocardial nutrition conditions. Amino acids (AAs) are essential nutrient metabolites for cell development and survival. This study aims to investigate the associations and prognostic value of plasma branched-chain amino acid/aromatic amino acid ratio (Fischer’s ratio, FR) in patients with left ventricular ejection fraction (LVEF) ≤ 50%. Methods The value of serum AAs was obtained from 441 cardiovascular patients by liquid chromatography-tandem, including 213 HF patients [all LVEF ≤ 50%, E/e’>14 (n = 101) and E/e’≤14 (n = 112)], and 228 controls without HF [(excluding HF with preserved ejection fraction (EF)]. Two-dimensional echocardiography and Doppler flow imaging determined LVEF and the ratio of early diastolic mitral inflow to mitral annular tissue velocities (E/e’). The abnormal LVEF (≤ 50%) refers to the definition of HF with reduced, mildly reduced, or improved EF. The logistic regression analysis was conducted to measure the FR index and the risk of cardiac dysfunction, and further confirmed by receiver-operating characteristic curves (ROC curve) analysis. In the prospective study, the 188 HF patients were followed up for a mean year (11.74 ± 1.44 months). The event-free HF endpoint or HF readmission was determined by Kaplan–Meier curves, and differences were assessed using log‐rank tests, respectively. Cox regression analysis was used to further assess the prognostic value of FR in HF. Results FR index decreased gradually along with the control group, HF with E/e’≤14 group, and HF with E/e’>14 group (3.73 ± 1.20 vs. 3.45 ± 0.94 vs. 3.18 ± 0.83, respectively, P < 0.001). Low FR index was associated with HF after full adjustment in all patients [odds ratio (OR): 2.072; 95% confidence interval (CI): 1.546–2.776; P < 0.001]. Meanwhile, low FR index was the independent risk factor for E/e’>14 in HF patients (OR:1.659; 95% CI:1.125–2.446; P = 0.011). The area under the ROC curve for predicting abnormal E/e’ was 0.762 (sensitivity 75.51%, specificity 65.05%) by multivariate logistic regression. Furthermore, the decreased FR values indicated poor HF endpoint or HF readmission in HF patients (all Log-rank P  < 0.01). The Cox regression analysis showed that low FR tertiles remained correlated to the risk of HF endpoint [hazard ratio (HR): 1.949; 95% CI: 1.006–3.778; P = 0.048]. Conclusions In all patients, low FR confers an increased risk for predicting HF. Decreased FR levels could also indicate increased left ventricular (LV) filling pressure in HF. In addition, a lower FR value was associated with higher HF endpoint events. Thus, FR can be a valuable indicator of heart function.